-12x-4(5+10x)=11(-3x+12)

Simple and best practice solution for -12x-4(5+10x)=11(-3x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12x-4(5+10x)=11(-3x+12) equation:


Simplifying
-12x + -4(5 + 10x) = 11(-3x + 12)
-12x + (5 * -4 + 10x * -4) = 11(-3x + 12)
-12x + (-20 + -40x) = 11(-3x + 12)

Reorder the terms:
-20 + -12x + -40x = 11(-3x + 12)

Combine like terms: -12x + -40x = -52x
-20 + -52x = 11(-3x + 12)

Reorder the terms:
-20 + -52x = 11(12 + -3x)
-20 + -52x = (12 * 11 + -3x * 11)
-20 + -52x = (132 + -33x)

Solving
-20 + -52x = 132 + -33x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '33x' to each side of the equation.
-20 + -52x + 33x = 132 + -33x + 33x

Combine like terms: -52x + 33x = -19x
-20 + -19x = 132 + -33x + 33x

Combine like terms: -33x + 33x = 0
-20 + -19x = 132 + 0
-20 + -19x = 132

Add '20' to each side of the equation.
-20 + 20 + -19x = 132 + 20

Combine like terms: -20 + 20 = 0
0 + -19x = 132 + 20
-19x = 132 + 20

Combine like terms: 132 + 20 = 152
-19x = 152

Divide each side by '-19'.
x = -8

Simplifying
x = -8

See similar equations:

| 9x=5x+9x-15 | | c(c-17)=0 | | 3x+6=2x+9 | | 4=-0.8 | | 5x+5=5x+x+2 | | 10x+6=6x-8+10x-16 | | 12*11-20= | | 16x-9=5x+12x-20 | | 10x+9-11-x=-2(2x+4)-3(2x-2) | | 5*1+2*(3-1)=6 | | n-14n-6=-5 | | n-14n-6=-6 | | 4x+3=5x+4x-3 | | 5=2x+5x-2 | | 5*5-(25/5)=20 | | 5*5-(25/5)= | | 4=4x-2+2x | | 75=3(6x-5) | | 9x-9=3x+6+x+6 | | 5x+45+-89=90+41 | | a^3-16ab^2=0 | | 5x+45-89=90+41 | | 4(5-6)+6x=6 | | -0.5x-7=-11 | | a(2x+3)=ax+12 | | 4a+-7a= | | 20-(3*2)+5= | | 20-(3*2)+5=19 | | 3-8x=35 | | 12.4x=37.2 | | 3x+5=13-x | | 8(3x+4)-2(4x-5)= |

Equations solver categories